Optimization of Edible Drinking Straw Characteristics from Banana Corm Starch and Stem Fiber with Klaras Leaf Dye - Deny Utomo; Rukmini Rukmini (University of Sultan Ageng Tirtayasa, 2025)
Environmental issues from single-use plastic straws have intensified globally, prompting the search for sustainable alternatives. This study aimed to optimize the formulation of edible drinking straws made from banana corm starch and banana stem fiber, enhanced with natural dye from klaras leaves. Optimization focused on physicochemical, visual, and sensory characteristics. The study consisted of two stages: (1) formulation of straws with varying starch-to-fiber ratios (P1S6–P6S1), and (2) evaluation of klaras leaf dye concentrations (0%, 3%, 6%, 9%). Parameters tested included thickness, water resistance at 10°C, 30°C, and 70°C, crude fiber content, color intensity (L*, a*, b*), and sensory attributes (taste, flavor, color, flowability). Statistical analyses used ANOVA, Tukey, Friedman, and a modified De Garmo method. The optimal formulation was P3S4 (4.5 g starch : 5.5 g fiber), with a thickness of 0.40 mm, highest water resistance (68.96%), and crude fiber content of 5.86%. Addition of 3% klaras dye (P3S4K1) yielded the darkest color (L* = 37.67), with a* = 2.08 and b* = 0.63, while achieving the highest sensory scores: taste (3.24), flavor (3.40), color (3.64), and flowability (3.68). These findings suggest that P3S4K1 is the most suitable formulation for edible straws, combining structural integrity, appealing appearance, and consumer acceptability.